Tantangan Pendidikan Karakter Melalui Penguatan Iman dan Takwa Anak Usia Dini di Era Digital - Sugianto Sugianto (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to identify and address the challenges of early childhood character education in facing the digital era full of exposure to inappropriate content. Through a qualitative approach with the Community-Based Research (CBR) method, this study involved early childhood, teachers, parents, and religious/community leaders in designing practical solutions. The identification results showed several challenges, such as exposure to inappropriate content, lack of parental supervision, and dependence on digital technology. The solutions implemented include increasing the role of parents, the use of positive content, alternative non-digital activities, and collaboration with educational institutions. By implementing a community-based faith and piety strengthening program, through religious value story activities, role-playing, and discipline activities, it is hoped that there will be an increase in understanding, positive behavioral changes in children, and more targeted use of digital technology. Recommendations include increasing parental digital literacy, compiling an educational curriculum that supports character strengthening, and providing a safe and child-friendly educational space. This study contributes to the understanding of the importance of strengthening the faith and piety of early childhood in the digital era and provides practical guidance for parents, educators, and the community in guiding early childhood towards the formation of good character according to religious values.